Effect of nutritional factors on growth and L-asparaginase production by three thermophilic coprophilous fungi - Ajmeera, Shanthi Priya; Rao, Vankudoth Koteswara; Sreelatha, B.; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Current Research in Microbiology Biotechnology, 2015)
The present study aimed to investigate the effect of nutritional factors on L-asparaginase production by three thermophilic caprophilous fungi (Thielavia terrestris, Malbranchea cinnamomea and Scytalidium thermophilum) was assessed in YES medium by substituting starch and L-asparagine so as to supply equal amount of carbon and nitrogen sources respectively. D-glucose, starch, maltose and mannitol were best source for growth and L-asparaginase production by all three thermophilic caprophilous fungi under investigation. Similarly L-asparagine, L-arginine, L-tyrosine and L-histidine were good nitrogen sources for both growth and L-asparaginase production. Production of the variance of the data showed the significant difference (P<0.05) among the three thermophilic caprophilous fungi with regards to carbon and nitrogen source.

Culture conditions for the production of thermostable lipase by thermomyces lanuginosus - Sreelatha, B.; Vankudoth, Koteswara Rao; Kumar, R. Ranjith; Girisham, Sivadevuni; Reddy, S. M. (Journal of Basic and Applied Sciences, 2016)
In the present investigation lipase production by three strains of thermophilic Thermomyces lanuginosus (GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14) was carried out in submerged fermentation process. Olive oil and triacetin (0.1%) were added to the basal medium, which stimulated the lipase production. The maximum lipase was produced by GSLMBKU-10 and GSLMBKU-13 in yeast extract starch medium supplemented with triacetin (0.1%). The optimum pH was recorded at 6.0, 6.5 and 7.0 by GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14 respectively. T. lanuginosus GSLMBKU-10 strains failed to produce lipase at pH 8.0. The optimum temperature for lipase production was observed at 45 °C by GSLMBKU-14 and GSLMBKU-10, while that for GSLMBKU-13 was at 50 °C. The marginal temperature ranged from 45 °C to 50 °C for both lipase production and vegetative growth by the three strains of T. lanuginosus under study. In conclusion, the GSLMBKU-13 strain was comparatively superior in the production of lipase than the other two strains under investigation.

Microbial synthesis of mammalian metabolites of spironolactone by thermophilic fungus thermomyces lanuginosus - Sreelatha, B.; Prasad, G. Shyam; Vankudoth, Koteswara Rao; Sivadevuni, Girisham (Steroids, 2018)
Mesophilic fungi are well recognized as models of mammalian drug metabolism. Thermophilic fungi remained unexplored despite having a unique mechanism of growing at higher temperatures and performing wide diverse reactions. The present investigation is directed to isolate a promising thermophilic fungal strain capable of biotransformation using spironolactone as a model drug. Two-stage fermentation protocol was followed for the process. The transformation of spironolactone was identified by HPLC and structure elucidation of the metabolites was done with the help of LC-MS/MS analysis and previous reports. A strain of Thermomyces lanuginosus isolated from decomposed banana peel waste was found to be most promising in transforming spironolactone to 4 metabolites viz.7α-thiospironolactone (M1) canrenone (M2), 7α-thiomethylspironolactone (M3) and 6β-OH-7α-thiomethylspironolactone (M4), the major mammalian metabolites reported previously. The synthesis of metabolites of spironolactone by T.lanuginosus similar to mammals clearly states that this fungus possess enzyme system similar to mammals. Hence, this fungus has the potential to use as a model organism for studying drug metabolism.